Influence of safflower oil (Carthamus tinctorius L.) on insulin resistance and ventricular hypertrophy in dyslipidemic mice (Research, Society and Development, 2020)
The regulation of lipid metabolism through the consumption of herbal medicines is a strategy to reduce the risk of cardiovascular diseases. Therefore, the aim of the study was to evaluate the effect of safflower oil on insulin resistance and left ventricular hypertrophy (LVH) in mice with the LDL receptor (LDLr -/-) with different diets. LDLr -/- mice were divided into four groups: C: standard diet; CCA: standard diet 2mg/kg/day of safflower oil; HL: hyperlipidic diet; HLCA: hyper dietalipid and 2mg/kg/day of safflower oil. After 15 days of experiment, total cholesterol and its fractions, triglycerides, C-reactive protein, insulin, glucose and adaptation to the Homa index were quantified. Histological slides with cardiac tissue were prepared and stained with hematoxylin and eosin, for general histological evaluation; and stained with picrosirius red to assess the collagen deposit area. The results obtained showed that safflower oil prevented the reduction of serum HDL levels and increased levels of CRP, partially prevented insulin resistance and hyperinsulinemia in the HLCA group mice. The use of safflower oil balanced the anti-hypertrophic factors in relation to the hypertrophic factors (hyperinsulinemia and inflammatory process), preventing LVH in the HLCA group mice. In conclusion, safflower oil prevented the development of LVH and partially insulin resistance.